Bax deletion prevents neuronal loss but not neurological symptoms in a transgenic model of inherited prion disease - Chiesa, Roberto (National Academy of Sciences, 2005)
Transgenic Tg(PG14) mice express a mutant prion protein containing 14 octapeptide repeats, whose human homologue is associated with an inherited prion dementia. These mice develop a progressive neurological disorder characterized by ataxia and cerebellar atrophy, with massive apoptotic degeneration of granule neurons. Bax, a proapoptotic gene of the Bcl-2 family, plays a key role in regulating cell death in the nervous system. To analyze the role of Bax in the Tg(PG14) phenotype, we crossed Tg(PG14) mice with Bax(-/-) mice to obtain Tg(PG14)/Bax(-/-) offspring. Bax deletion effectively rescued cerebellar granule neurons from apoptosis, implying that these cells die via a Bax-dependent process. Surprisingly, however, the age at which symptoms began and the duration of the clinical phase of the illness were not altered in Tg(PG14)/Bax(-/-) mice. In addition, Bax deletion failed to prevent shrinkage of the molecular layer of the cerebellum and loss of synaptophysin-positive synaptic endings. Our analysis indicates that synaptic loss makes a critical contribution to the Tg(PG14) phenotype. These results provide insights into the pathogenesis of prion diseases and have important implications for the treatment of these disorders.